Beyond Prohibitions: Unveiling the Hidden Dynamics of Islamic Economics and Finance - Burhan Uluyol (Journal of Islamic Monetary Economics and Finance, 2026)
Despite theoretical differences between conventional and Islamic finance, critics argue that Islamic finance remains operationally similar to conventional finance. This apparent convergence in substance has led to growing disillusionment among stakeholders, prompting calls for a reassessment of the objectives and principles underlying Islamic finance. The objective of this study is twofold: first, to conduct a comprehensive comparative analysis between Islamic finance and conventional finance, and second, to explore the hidden dynamics of Islamic economics and finance by investigating its special theoretical features. By conducting intensive library research and reviewing main studies in Islamic economics and Finance, this study examines the salient features of Islamic economics and finance. The study identifies several hidden dynamics, including the role of money as a medium of exchange, prohibition of debt securitization, financing real sector development, the role of Islamic finance in infrastructure development, and the impact of Shariah screening mechanisms on stock market crashes. By examining the salient features of Islamic Economics and Finance, this research aims to provide theoretical insights that will contribute to academic literature, while also guiding regulators and industry practitioners in innovating financial products that more authentically embody the ethical spirit of Islamic finance.